KONSEP USWATUN HASANAH DALAM PENDIDIKAN ISLAM PADA ERA SOCIETY 5.0 PERSPEKTIF AL-QURAN DAN HADIS - Utami, Lia Dwi; Nursiah; Irhas Sabililhaq (Universitas Yudharta Pasuruan, 2023)
The background of this research emerged as a response to the rapid development of the current situation in the era of society 5.0, which had a significant impact on the education and character of students. As stakeholders in education, it is important for us to respond to this because the purpose of education is to shape the morals of students. The purpose of this study is to describe the concept of uswatun hasanah in Islamic education in the era of society 5.0 based on the perspective of the Qur'an and Hadith. This research uses a qualitative approach with a type of literature study. The data collection technique uses dpkumentasi with content analysis. The results of the research show that Islamic education is an attempt to develop human potential in order to achieve a level of perfection. Clearly, Islamic education aims to enable humans to fulfill their role as creatures of Allah SWT who are faithful, knowledgeable, and have good morals. In the context of Islamic education, the exemplary method (uswah hasanah) has an important and significant role in creating a moral, spiritual and social ethos in students. The concept of exemplary or modeling has been taught in the Al-Qur'an, such as QS. Al-Ahzab verse 21 and Al-Baqarah verse 44, as well as several hadiths as evidence that educators should apply this method by providing positive examples that students can emulate. The example shown by educators has a significant influence on children's education. In the context of Islamic Education, educators play the role of warasatu al-anbiya, whose mission is to be a mercy to all nature. This mission involves inviting humans to submit and obey God's laws. The mission was then expanded to cover personality development that is monotheistic, creative, charitable, and has a noble character.